A Rare Case of Splenic Pneumocystis jirovecii in a HIV-Positive Patient. (10th June 2020) - Abbas, Hafsa; Patel, Harish; Baiomi, Ahmed; Niazi, Masooma; Vakde, Trupti; Chilimuri, Sridhar
Abstract : Introduction . Human immunodeficiency virus (HIV) positive individuals with the CD4 count less than 200 cells/mm 3 are at risk for opportunistic infections. Pneumocystis jirovecii, a fungal pathogen, is a common cause of opportunistic infections with predominantly pulmonary involvement. Disseminated P. jiroveciii infection presenting with hepatosplenic lesion is extremely rare. Case Summary . A 31-year-old male with HIV with and acquired immunodeficiency syndrome (AIDS) presented with diarrhea for 3 weeks. He had splenomegaly and inguinal lymphadenopathy on physical examination. Laboratory parameters revealed anemia and hypoalbuminemia, while stool studies for infectious etiology and fecal leucocyte were negative. Computed tomography (CT) of the chest and abdomen depicted consolidation of the lungs and a large splenic mass. He underwent fiberoptic bronchoscopy with transbronchial biopsy which was consistent with P. jirovecii pneumonia. He also had a ultrasound-guided core biopsy of the splenic mass which revealed necrotizing granulomas with Pneumocystis jirovecii infection on Grocott-Gomori's methenamine silver (GMS) stain and was initiated on treatment for P. jirovecii with sulfamethoxazole with trimethoprim. Conclusion . Malignancy and atypical infection are key differentials in patients presenting with hepatosplenic lesions. HIV positive patients are at increased risk of AIDS-related lymphoma. Tissue diagnosis is often required for further evaluation. Disseminated P. jirovecii presenting with splenic mass and liver lesion is extremely rare.